Diversity and Feeding Guilds of Birds in Way Rilau Research Station, Core Block of KPH Batutegi, Lampung Province - Iswandaru, Dian; Octavia, Anggi; Hidayat, Aris; Sari Dewi, Bainah; Huda, Robithotul; Subagio, Aris; Nedi; Ismail (Talenta Publisher, 2026)
Protected forests are forest areas protected by law to maintain the balance of their ecosystems. The reciprocal relationship between birds and their environment can serve as an indicator of habitat condition, as birds are highly sensitive to environmental changes. The Way Rilau Research Station, situated in Lampung Province, is a protected forest that serves as a habitat for a diverse range of bird species. Therefore, the purpose of this research is to obtain data on species diversity, species richness, species evenness, and bird species dominance. Data collection in this study was conducted using a combination of point-count and line-transect methods. Observations were conducted in the morning (6–9 am) and the afternoon (3–6 pm). The results showed that 76 bird species from 37 families were recorded, totaling 382 individuals. The diversity index (H') value is 3,836, with a high category, and the species richness index (R) value is 13,370, which is categorized as high. The bird species evenness index (E) value is 0.886, which is classified as stable, while the species dominance index (C) value is 0.034, which indicates no species dominates. Based on the bird food guild type, the insectivore group dominates with 55 species (71.05%). The frugivore group with 12 species (17.11%), the carnivore group with four species (5.26%), the next dominance is the omnivore group with four species (5.26%), and the piscivore group with one species (1.32%)